The modernist Anthropocene : nonhuman life and planetary change in James Joyce, Virginia Woolf and Djuna Barnes - Adkins, Peter (Edinburgh critical studies in modernist culture., 2022)
Provides the first book-length analysis of modernism and the AnthropoceneProvides new and comparative readings of James Joyce, Djuna Barnes and Virginia Woolf, demonstrating how ecocriticism and posthumanism can open up new ways of understanding modernismIncludes new discoveries from Djuna Barnes's archive that expand how we perceive her writingContributes to the turn in modernist studies towards the synthesis of historicism and theory, examining modernist fiction in the context of early-twentieth century scientific, environmental, and socio-political developments, while also bringing modernism into dialogue with contemporary theoryThe Modernist Anthropocene examines how modernist writers forged new and innovative ways of responding to rapidly changing planetary conditions and emergent ideas about nonhuman life, environmental change and the human species. Drawing on ecocritical analysis, posthumanist theory, archival research and environmental history, this book resituates key works of modernist fiction within the ecological moment of the early twentieth century, a period in which new configurations of the relationship between human life and the natural world were migrating between the sciences, philosophy and literary culture. The author makes the case that the early twentieth century is pivotal in our understanding of the Anthropocene both as a planetary epoch and a critical concept. In doing so, he positions James Joyce, Djuna Barnes and Virginia Woolf as theorists of the modernist Anthropocene, showing how their oeuvres are shaped by, and actively respond to, changing ideas about the nonhuman that continue to reverberate today.